FABRICATION OF POROUS CARBONATE APATITE BASED ON THE DISSOLUTION-PRECIPITATION OF CALCIUM SULFATE HEMIHYDRATE - Dede Arsista; Yosi Kusuma Eriwati; Siti Triaminingsih; Sunarso Sunarso (FKG Unlam, 2019)
Background: Carbonate apatite (C-Ap) has been used as a bone replacement material because it has osteoconductive properties. The pores contained in C-Ap are useful so that cells can diffuse during new bone formation. Calcium sulfate hemihydrate (CaSO4.1/2H2O) precursor has been used as it possesses Ca2+ ions, while polymethylmetacrylate (PMMA) is chosen because it is easily burned out at low temperatures. Objectives: To fabricate porous carbonate apatite based on a calcium sulfate hemihydrate precursor using the dissolution-precipitation method and identify its phases by X-ray diffraction. Methods: The pores were made by crushing polymethyl methacrylate (PMMA) granules and sieving them to sizes of 300–500 µm. Specimens of porous carbonate apatite were prepared from a mixed calcium sulfate hemihydrate precursor with different quantities of porogen: 0 wt% PMMA (n = 60 ), 25 wt% PMMA ( n = 60 ), and 50 wt% PMMA ( n = 60 ). Calcium sulfate hemihydrate containing PMMA was mixed with distilled water at a water: powder ratio of 0.5 ml: 1g. Calcium sulfate dihydrate specimens were placed in an oven at 700˚C for 4 h to burn out the PMMA, resulting in porous calcium sulfate anhydrate. This was then immersed in phosphate mixed solution (Na3PO4) and carbonate solution (Na2CO3) for 1, 3, and 5 days to obtain carbonate apatite through a precipitation-dissolution process. An X-ray diffraction technique (X-Ray Diffractometer, PANalytical XPert PRO) was used to analyze each group of specimens to identify the phase formation of porous carbonate apatite. Results: The X-ray diffraction pattern showed peaks of carbonate apatite in all specimens with 0, 25, and 50 wt% PMMA in 1, 3, and 5 days of immersion, except in the 0 wt% specimens at 1 day. The carbonate apatite diffraction peaks were at 2q = 25.9°, 29.2°, 32°, and 34°. The earliest complete formation of the carbonate apatite phase was identified from the preparation of porous anhydrous CaSO4 with porogen of 50 wt% PMMA immersed for 1 day. Conclusion: Porous carbonate apatite can be produced from precursors of calcium sulfate hemihydrate and porogen of PMMA via a precipitation-dissolution method.